The Lack of Norms in the Settlement of Land Disputes between Indigenous Communities and Land Use Rights Holders within the Framework of National Agrarian Law Reform - Mulyana; Richard (Journal of Legal and Cultural Analytics, 2026)
The purpose of this study is to examine the disparity in standards for settling land disputes between communities governed by customary law and those who possess Land Use Rights (HGU) and to develop a fair and legally sound reform strategy for national agrarian law. The Republic of Indonesia's 1945 Constitution, Law Number 5 of 1960 Governing Basic Agrarian Principles, and other relevant regulations are studied using normative juridical research with a legislative methodology and a conceptual approach. The study's findings show that while customary law communities and customary rights are acknowledged, there is no explicit normative framework for governing interactions and resolving conflicts with HGU holders. The gap in norms is reflected in the absence of standard procedures for recognizing customary territories before granting HGU, disharmony of cross-sectoral regulations, and the absence of a specific dispute resolution mechanism that accommodates the characteristics of customary law. This condition results in legal uncertainty and structural injustice for customary law communities. Therefore, it is necessary to reconstruct agrarian law through regulatory harmonization, strengthening the recognition of customary rights, and establishing a dispute resolution mechanism that is more inclusive and responsive to legal pluralism in Indonesia.